What is the effect of successive segmental repair on the mutual intelligibility of ELF users?. (December 2021) - O'Neal, George
Abstract: This study assessed the effect of successive segmental repair on the mutual intelligibility of ELF users using a quasi-experimental design. Twenty-six pairs of ELF users completed three English phonemic discrimination tasks, once a week for three weeks, in which maintaining intelligible pronunciation was essential to the completion of the tasks. The pairs were randomly assigned to one of two conditions: an interaction condition or a no interaction condition. Pairs in the interaction condition could segmental repair when mutual intelligibility faltered; pairs in the no interaction condition could not. Although pairs in the interaction condition were consistently more mutually intelligible than pairs in the no interaction condition, pairs in the interaction condition did not become successively more mutually intelligible across the three weeks. Accordingly, segmental repair seems to facilitate the development of mutual intelligibility, but successive segmental repairs do not necessarily cumulatively increase mutual intelligibility.